Meteorological and chemical impacts on PM2.5 during a haze episode in a heavily polluted basin city of eastern China. (July 2019) - Bao, Zhier; Chen, Linghong; Li, Kangwei; Han, Lixia; Wu, Xuecheng; Gao, Xiang; Azzi, Merched; Cen, Kefa
Abstract: Haze formation involves many interacting factors, such as secondary aerosol formation, unfavourable synoptic conditions and regional transport. The interaction between these factors complicates scientific understanding of the mechanism behind haze formation. In this study, we investigated the factors resulting in haze events in Longyou, a city located in a basin in China. Aerosol samples of PM2.5 were collected for subsequent chemical composition analysis between 11 January and 5 February 2018. The impacts of wind on PM2.5, SO2 and NO2 concentrations were analysed. Besides, the origin of air parcels and potential sources of PM2.5 were analysed by backward trajectory, potential source contribution function (PSCF) and concentration-weighted trajectories (CWT). Among the water-soluble ions identified, NO3 − had the highest concentration, with further analysis demonstrating the haze evolution was mainly driven by the reactions involving NO3 − formation. The dramatic increase of nitrate is mainly due to the homogeneous reaction of nitric acid with ammonia, while sulfate is likely due to heterogeneous reactions of NO2, SO2 and NH3 . The average wind speed was less than 2 m/s during the aerosol sampling period, which could be considered as a stagnant state. Pollutants emitted by industrial area located in the northeast Longyou were probably brought to observation sites by continuous wind from northeast and accumulated gradually. Air parcels originating from the northeast of Zhejiang province also had large effects on haze pollution in Longyou. Together, our results showed that rapid secondary aerosol formation and unfavourable synoptic conditions are the main factors resulting in haze pollution in Longyou. Graphical abstract: Image 1 Highlights: Unfavourable meteorological conditions resulted in the accumulation of PM2.5 and NO2 . The evolution of haze pollution was mainly driven by the reactions involving NO3 − formation. Homogeneous reactions might play an important role nitrate formation. Two haze episodes with the same shapes were affected by different transport paths.